Implementation of communication system between Siemens PLC S7-1200 with Omron PLC CP1L-EL20DT1-D for induction motor speed controller - Yusuf, Muhamad; Rohman, Abdul (Proceedings; 2020: The 2nd International Conference on Applied Science and Technology (iCAST) 2019 Proceeding, 2020)
Nowdays, it has entered the era of the Industrial Revolution 4.0 where information and communication technology plays an important role almost in all fields such as transportation, industry, education and other fields. The Industrial Revolution 4.0 requires that all equipments or systems are connected to one another. At present, many equipments in the field of industrial automation have not integrated yet. The main device that must be connected in a control system is a PLC, because it is a data storage and control center. Some problems will arise if the PLCs are not connected to each other, such as asynchronous data which managed by each PLC, offline data recording and monitoring the performance of each PLC takes a relatively long time. This research discusses the multi PLC communication system for induction motor speed regulation. Induction motor is one type of motor that is widely used in industry because it is cheap and reliable. The communication media is used for communication between PLCs is modbus. The results showed that communication between PLCs could worked well with the master model (PLC Siemens) - slave (PLC Omron). The system had a steady state error of 17.07% with a maximum speed of 1267.6 rpm.